Gross motor coordination and weight status of Portuguese children aged 6-14 years - Antunes, António M. (2021)
Objectives: To construct age- and gender-specific percentiles for gross motor coordination (MC) tests and to explore differences in gross MC in normal-weight, overweight and obese children. Methods: Data are from the “Healthy Growth of Madeira Study,” a cross-sectional study carried out in children, aged 6–14 years. All 1,276 participants, 619 boys and 657 girls, were assessed for gross MC (K€orperkoordinations Test fur Kinder, KTK), anthropometry (height and body mass), physical activity (Baecke questionnaire) and socioeconomic € status (SES). Centile curves for gross MC were obtained for boys and girls separately using generalized additive models for location, scale and shape. Results: A significant main effect for age was found in walking backwards and moving sideways. Boys performed significantly better than girls on moving sideways. At the upper limit of the distributions, interindividual variability was higher in hopping on one leg (girls) and jumping and moving sideways (boys and girls). One-way ANCOVA, control ling for age, physical activity and SES, indicated that normal-weight children scored significantly better than their obese peers in all gross MC tests. Overweight boys and girls also scored significantly better than their obese colleagues in some MC tests. Conclusions: These centile curves can be used as reference data in Portuguese children and youth, aged 6–14 years. Being overweight or obese was a major limitation in MC tests and, therefore, of the children’s health- and performance related physical fitness.